Surface configuration of CO adsorbed on nanostructured Pt electrodes probed using broadband sum frequency generation spectroscopy. Issue 67 (23rd July 2020) - Huang-Fu, Zhi-Chao; Song, Qian-Tong; He, Yu-Han; Liu, Xiao-Lin; Wang, Jing-Jing; Sun, Shi-Gang; Wang, Zhao-Hui
Abstract : Inhomogeneity of adsorbed CO introduced by the aggregation of Pt nanoparticles. Abstract : Using broadband sum frequency generation (BB-SFG) spectroscopy, the effect of surface structure on the adsorption states of linearly bonded CO (COL ) on a Pt electrode was thoroughly analyzed. Two overlapped SFG peaks with different linewidths and electrochemical Stark slopes were identified, which correspond to COL in different surface configurations.